Gait differences between K3 and K4 persons with transfemoral amputation across level and non-level walking conditions. (December 2018) - Sturk, James A; Lemaire, Edward D; Sinitski, Emily; Dudek, Nancy L; Besemann, Markus; Hebert, Jacqueline S; Baddour, Natalie
Background: A transfemoral amputee's functional level can be classified from K-level 0 (lowest) to K-level 4 (highest). Knowledge of the biomechanical differences between K3 and K4 transfemoral amputation could help inform clinical professionals and researchers in amputee care and gait assessment. Objectives: Explore gait differences between K3- and K4-level transfemoral amputation across different surface conditions. Study design: Cross-sectional study. Methods: Four K3 and six K4 transfemoral amputation and 10 matched able-bodied individuals walked in a virtual environment with simulated level and non-level surfaces on a self-paced treadmill. Stability measures included medial-lateral margin of stability, step parameters, and gait variability (standard deviations for speed, temporal-spatial parameters, root-mean-square of medial-lateral trunk acceleration). Results: K3 walked slower than K4 with wider steps, greater root-mean-square of medial-lateral trunk acceleration, and greater medial-lateral margin of stability standard deviations, indicating their stability was further challenged. K3 participants had greater asymmetry in double support time and trunk acceleration root-mean-square in the medial-lateral direction, but similar asymmetry overall. K3 participants had larger differences from AB and in more parameters than K4, although K4 differed from AB in trunk acceleration root-mean-square in the medial-lateral direction, walking speed, and double support time standard deviations. Conclusion: The findings improve our understanding of K3 and K4 transfemoral amputation gait on slopes and simulated uneven surfaces. Clinical relevance: High performing and community ambulatory transfemoral amputees cannot match the ambulatory abilities of ablebodied individuals. Understanding gait differences between these groups under conditions that challenge balance is required to develop rehabilitation protocols and prosthetic componentry targeted at improving transfemoral amputee gait and overall mobility in their chosen environment.